Colloid scintigraphy in non-alcoholic steatohepatitis: A conventional diagnostic method for an emerging disease - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2006)
Aim Non-alcoholic steatohepatitis (NASH) is a progressive liver disease characterized by diffuse fatty infiltration and Kupffer cell dysfunction which contributes to its pathogenesis. Since the liver biopsy, which is considered the 'gold standard' in diagnosing NASH, has some limitations other imaging methods have been explored as alternatives. Colloid scintigraphy is a good method reflecting Kupffer cell activity and we found it worthwhile to evaluate this technique in NASH. We aimed to present the common scintigraphic features and their clinicopathologic correlations in NASH. Methods Twenty-two new patients (11 female, mean age 43.7 +/- 10.8) with biopsy-proven NASH underwent colloid liver scintigraphy. The dynamic, static and SPECT images were performed after intravenous injection of 185MBq Tc-99m tin colloid. Hepatic perfusion, blood pool clearance time, colloid shift to spleen and bone marrow were assessed and liver right/left lobe ratio was calculated. Results The values calculated on static and tomographic (SPECT) images showed good correlation. Liver right/left lobe ratio was altered in all patients. Blood pool clearance time was prolonged in seven (32%) but hepatic perfusion was normal in all patients. Colloid shift to the spleen was observed in 55% of patients using SPECT analysis. No correlation between scintigraphy parameters and histological or biochemical findings were observed. Conclusion Altered liver right/left lobe ratio was the universal finding in all our NASH patients. Other common scintigraphic features of NASH include colloid shift to spleen and prolonged blood pool clearance time. Liver scintigraphy might be a promising non-invasive tool in the follow-up of NASH patients in therapeutic trials.
Keywords: non-alcoholic steatohepatitis; colloid scintigraphy; right/left lobe ratio; splenic shift; Kupffer cell function; ALCOHOLIC LIVER-DISEASE; FATTY LIVER; COMPUTED-TOMOGRAPHY